Cross-National Comparisons of Income Distribution: The Income Distribution Guideline Needs of Microdata Users as Seen from the Perspective of the Luxembourg Income Study - Timothy Michael Smeeding (Luxembourg Income Study (LIS), 1996)
The Luxembourg Income Study has worked for more than 14 years to improve cross-national comparability of microdata. Work on comparative issues related to microdata based on income distribution studies must start with a bottom-up microdata and experience with cross-national comparability of household income survey data. This paper examines the contributions that the Luxembourg Income Study can make to the creation of Income Distribution Guidelines.
Keywords: 330; Einkommensverteilung; Mikroökonomik; Industrieländer